2004
DOI: 10.1128/aem.70.3.1723-1734.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity and Heterogeneity in Sandy Subsurface Soils

Abstract: Microbial community diversity and heterogeneity in saturated and unsaturated subsurface soils from Abbott's Pit in Virginia (1.57, 3.25, and 4.05 m below surface) and Dover Air Force Base in Delaware (6.00 and 7.50 m below surface) were analyzed using a culture-independent small-subunit (SSU) rRNA gene (rDNA)-based cloning approach. Four to six dominant operational taxonomic units (OTUs) were identified in 33 to 100 unique SSU rDNA clones (constituting about 40 to 50% of the total number of SSU rDNA clones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 52 publications
10
79
0
2
Order By: Relevance
“…The spatial structure in other groups may be detectable beyond the scale of our study. For example, spatial structure in nematode populations can be detected at the scale of more than tens of metres (Liang et al, 2005), whereas bacterial communities shift within a few millimetres because of differences in soil microhabitats (Zhou et al, 2004). Soil animals comprise organisms of very different size and mobility, which may blur their distribution patterns because of multiple conflicting signals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial structure in other groups may be detectable beyond the scale of our study. For example, spatial structure in nematode populations can be detected at the scale of more than tens of metres (Liang et al, 2005), whereas bacterial communities shift within a few millimetres because of differences in soil microhabitats (Zhou et al, 2004). Soil animals comprise organisms of very different size and mobility, which may blur their distribution patterns because of multiple conflicting signals.…”
Section: Discussionmentioning
confidence: 99%
“…Such a sampling scheme enables to account for soil patchiness on a millimetre scale (Zhou et al, 2004) and provides sufficient replication for distance classes from 0.01 to 32 m. The central sampling spot was randomly selected with the constraint that it had to comprise a uniform 40.25-m 2 patch of microtopography and ground vegetation and lie 41 m from any surrounding tree (41 cm diameter at the base). Around each sample, a 0.5 × 0.5 m 2 quadrat was established, and the cover of understorey plant species was recorded.…”
Section: Sampling and Site Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the microbial groups that are abundant in the soil, bacteria have been the most extensively studied. Nevertheless, our understanding of the spatial distribution patterns of bacterial diversity is limited, mainly because most studies are limited to local scales (Navarro-Gonzalez et al, 2003;Zhou et al, 2004). Recent large-scale surveys have revealed that different ecosystems support unique microbial populations (Zhou et al, 2002;Fierer and Jackson, 2006;Green and Bohannan, 2006;Vishniac, 2006;Adler and Levine, 2007), giving rise to the notion that microbial populations can exhibit geographic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, soil characteristics of both P and NP areas resulted to be similar. Notwithstanding the heterogeneity of microbial distribution in the soil (Zhou et al 2004 Zhou, J, Xia, B, Huang, H, Palumbo, AV and Tiedje, JM. 2004.…”
Section: Discussionmentioning
confidence: 99%